Companhs de camins, Robert Lafont et le PCF - Marie-Jeanne Verny (Lengas)
Robert Lafont's relations with the PCF and its satellites took many forms between the post-war years and the early 1980s, in a variety of political and historical contexts. They essentially took two forms: on the one hand, literary collaboration with Communist publications and publishing houses, and on the other, more political relations within the framework of Lafont's Occitanist project. This article examines these relationships and their context, both from the outside, based on historical documents, and from the inside, based on Lafont's own point of view. It will also highlight some of the communist figures with whom he was associated.